Extracurricular Program for Girls to Improve Competencies and Self-Concept in Science and Technology - Erica Ruiz-Bartolomé; Ileana M. Greca (MDPI AG, 2023)
The gender gap in STEM areas is still a reality that constitutes a global concern. Many initiatives have sought to strengthen the scientific-technological aspirations of girls, among them extracurricular programs such as the one we present here. Its design is based on the available scientific evidence to promote female interest and self-concept in those areas. In this study, we analyze the impact of the extracurricular activities on the development of competencies and perceptive self-evaluation skills among eight girls aged between 8 and 11 years old regarding science and technology. The results showed the effectiveness of the extracurricular activities both for the development of skills and for the improvement of levels of self-concept, interest, and participation, which leads us to highlight the need to promote initiatives of this sort in order to overcome gender stereotypes and to achieve equality.